Influence of spouting period on microbiological and nutritional attribute of sesame seed flour - Joseph Oghenewogaga Owheruo; Patrick Othuke Akpoghelie; Great Iruoghene Edo; Emad Yousif; Agatha Ngukuran Jikah; Priscillia Nkem Onyibe; Ufuoma Ugbune; Endurance Fegor Isoje; Ufuoma Augustina Igbuku; Helen Avuokerie Ekokotu; Ephraim Evi Alex Oghroro; Joel Okpoghono; et al. (Discover Food)
Abstract This present research was carried out to study the effects of spouting periods on the, proximate composition, mineral content, ant-nutritional factor and microbiological content of sprouted sesame flour. Sesame seeds were soaked in water for 6 h and sprouted for period of 0 h, 24 h, 48 h, 72 h and 96 h. The sprouted seeds were dried at 70 °C for 55 min and milled into flour. The flour was assayed for proximate composition, mineral content, anti-nutrient content and microbiological using standard methods. Results showed that increasing the spouting periods of sesame seed significantly (P < 0.05) increased the protein (28.92–44.21 g/100 g) and ash (9.13–9.93 g/100 g) but decreased moisture (8.02–4.67 g/100 g), crude fibre (13.89—9.82 g/100 g), carbohydrate (16.75–4.10 g/100 g) and crude fat (23.29–23.27 g/100 g) of the flour respectively. The same applies for the mineral contents; calcium (460.07–477.07 mg/100 g) magnesium (390.06–419.07 mg/100 g). From 0 to 96 h sprouting time, the viable count increased from 6.40 ± 0.04 × 103 to 8.20 ± 0.05 × 103 cfu/g, yeast count from 7.60 ± 0.07 × 103 to 7.82 ± 0.04 × 103 cfu/g, and mold count from 18.44 ± 1.08 × 103 to 24.15 ± 1.34 × 103 cfu/g respectively with no Coliform counts. The data obtained was within the standard acceptable microbiological limit. The study has shown that increase in sprouting period improved the nutrient and microbiota composition of the sesame seed flour.